2018
DOI: 10.1161/hypertensionaha.118.11382
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography and Adrenal Venous Sampling in the Diagnosis of Unilateral Primary Aldosteronism

Abstract: Abstract-Unilateral primary aldosteronism is the most common surgically correctable form of endocrine hypertension and is usually differentiated from bilateral forms by adrenal venous sampling (AVS) or computed tomography (CT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
96
3
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(109 citation statements)
references
References 32 publications
(42 reference statements)
7
96
3
3
Order By: Relevance
“…In their prospective study, CT localization of APAs demonstrated equivalent sensitivity and specificity to AVS. However, study participants had visible adrenal lesions >7 mm and a large proportion had hypokalaemia (or “low normal” serum potassium) at the time of presentation . When applied to the broader characteristics of patients diagnosed with PA, the sensitivity of CT remains low when adhering to criteria based on the patient characteristics within the SPARTACUS study.…”
Section: Discussionmentioning
confidence: 99%
“…In their prospective study, CT localization of APAs demonstrated equivalent sensitivity and specificity to AVS. However, study participants had visible adrenal lesions >7 mm and a large proportion had hypokalaemia (or “low normal” serum potassium) at the time of presentation . When applied to the broader characteristics of patients diagnosed with PA, the sensitivity of CT remains low when adhering to criteria based on the patient characteristics within the SPARTACUS study.…”
Section: Discussionmentioning
confidence: 99%
“…The differentiation of unilateral from bilateral forms is achieved by computed tomography (CT) or adrenal venous sampling (AVS). AVS is the recommended approach by the Endocrine Society Guideline 11 because of the lack of specificity and sensitivity of CT [12][13] . The objective of adrenalectomy is to resolve excessive aldosterone production, normalize plasma potassium concentrations (if the patient was hypokalemic pre-surgically), and to normalize or at least improve the elevated blood pressure which is characteristic of the disorder.…”
Section: Introductionmentioning
confidence: 99%
“…AVS is a gold standard test to confirm the subtype classification of PA. In fact, a recent study reported that patients diagnosed by CT have a decreased likelihood of achieving complete biochemical success compared with a diagnosis by AVS . Therefore, AVS should basically be performed in most patients with PA who undergo adrenalectomy, if indicated.…”
Section: Discussionmentioning
confidence: 99%